Reopening Universities without Testing During COVID-19: Evaluating a Possible Alternative Strategy in Low Risk Countries - Xi, Jing Yang (Sunny); Chan, Wai Kin (Victor) (Archives of Clinical and Biomedical Research, 2022)
Worldwide, students’ safety and access to education are major concerns during COVID-19. The reopening of universities in high risk countries during Fall 2020 resulted in numerous outbreaks. While regular screening and testing on campus can prevent the transmission of SARS-CoV-2, they are extremely challenging to implement due to various reasons such as cost and logistics. However, for low risk countries with minimal to no community spread, our study suggests that universities can fully reopen without testing, if students self-quarantine for 14 days on arrival and adopt proper nonpharmaceutical interventions (NPIs). This alternative strategy might save institutions millions of dollars while allowing all students to participate in offline education. We design an agent-based SEIR model to simulate virus transmission in oncampus dormitories and test the effectiveness of six NPIs after students arrive. Assuming one initially infected student, results indicate that transmission between roommates causes the most infections with visitors, ground floors, and elevators being the next main contributors. Counterintuitively, limiting density or population in dormitories are not impactful at flattening the curve. However, adopting masks, limiting movement, and increasing the frequency of cleaning can effectively halt infection and prevent outbreak, allowing for classes and activities to potentially resume as normal. Based on simulation results, we also suggest an optimal reopening strategy that minimizes students’ infection risk, while maximizing convenience of living and access to education.